2019
DOI: 10.3390/app9183739
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Adaptive “Neuro-Fuzzy” Inference System in Modeling Cutting Temperature during Hard Turning

Abstract: The machining of hard materials with the most economical process is a challenge that is the aim of production systems. Increasing demands of the market require a hard processing hardened steel in order to avoid finishing grinding. This research considers the turning of hardened steel without cooling with two types of tools: cubic boron nitride (CBN) and hard metal (HM) inserts. To estimate the influence of machining conditions on cutting temperature, a central composition design with three factors on five leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In the ANFIS structure, rst layer is called fuzzi cation layer, a collection of fuzzy if then rules with triangular membership function for this work and second layer: product layer, third layer: normalized layer, fourth layer: defuzzi cation layer and fth layer: output layer. Description of ANFIS implementation can be found in literature (Babajanzade Roshan et al 2013; Teimouri and Sohrabpoor 2013; Kumar and Hynes 2019; Savkovic et al 2019). The 18 training data set are known to be input training vectors and the number of epochs for ANFIS training was tried from 3 to 100 and it was found that convergence of results began from 2nd epoch and nally the number of epochs was set to 30.…”
Section: Adaptive Neuro Fuzzy Inference Systemmentioning
confidence: 99%
“…In the ANFIS structure, rst layer is called fuzzi cation layer, a collection of fuzzy if then rules with triangular membership function for this work and second layer: product layer, third layer: normalized layer, fourth layer: defuzzi cation layer and fth layer: output layer. Description of ANFIS implementation can be found in literature (Babajanzade Roshan et al 2013; Teimouri and Sohrabpoor 2013; Kumar and Hynes 2019; Savkovic et al 2019). The 18 training data set are known to be input training vectors and the number of epochs for ANFIS training was tried from 3 to 100 and it was found that convergence of results began from 2nd epoch and nally the number of epochs was set to 30.…”
Section: Adaptive Neuro Fuzzy Inference Systemmentioning
confidence: 99%
“…In Layer 1, the parameters are referred to as the premise parameters (Savkovic et al, 2019) whilst the parameters in Layer 4 are called the consequent parameters in Layer 4 (Kumar and Vaidehi, 2017).…”
Section: (6)mentioning
confidence: 99%
“…In recent years, several researchers have focused on developing comprehensive modeling techniques to predict the machining performance through considering diverse input parameters. Although different statistical approaches have been proposed for modeling the machining processes, such as regression models [ 14 ], support vector machines [ 15 ], and finite element models [ 16 ], soft computing techniques such as fuzzy logic [ 17 ], artificial neural networks [ 18 ], and adaptive neuro-fuzzy inference system (ANFIS) [ 19 ] are prominent in predicting the performance of machining processes because of their progressive computational capability.…”
Section: Introductionmentioning
confidence: 99%